New and future perspectives in familial Mediterranean fever and other autoinflammatory diseases - Veysel Çam; Hülya Ercan Emreol; Seza Ozen (Archives of Rheumatology, 2024)
Systemic autoinflammatory diseases are a group of disorders characterized by sterile episodes of inflammation resulting from defects in the innate immune system. In contrast to classical autoimmune diseases, where circulating autoantibodies and the adaptive immune system are involved, these conditions involve excessive presence of proinflammatory cytokines leading to inflammatory attacks. Excessive cytokine production, functional mutations in regulatory pathways, excessive interferon production, defects in the nuclear factor-kappa B signaling pathway, abnorARCHmal protein folding, and complement activation are the mechanisms leading to autoinflammatory diseases. A defect in the mTOR pathway and trained immunity are newly discovered possible causes in pathogenesis. Early onset and severe forms of classical rheumatological diseases have been more frequently associated with autoinflammatory diseases in the last decade. Therefore, monogenic autoinflammatory diseases should be considered in rheumatic diseases with family history, consanguinity, early onset, and severe disease. The combination of functional and genotyping research will help to identify unclassified patients. The optimal treatment strategy remains uncertain, functional studies such as interferon signature and cytokine profiling, may prove valuable in guiding the treatment process. Stem cell transplantation strategies in autoinflammatory diseases with partial response to biological therapies can be considered. Autoinflammatory diseases are becoming increasingly complex and are bringing new perspectives to already known rheumatic diseases. Although we have effective treatments, we are still far from personalized recommendations.